An ocean for the Global South: Brazil and the zone of peace and cooperation in the South Atlantic - Abdenur, A. E. (2018)
In this article, we analyse an instance of revitalisation of a dormant interregional organisation dating back to the Cold War: the Zone of Peace and Cooperation of the South Atlantic (ZOPACAS), initially launched by South American and African states in 1986 through the UN General Assembly. Drawing on the concepts of “consensual hegemony” we argue that the current phase of ZOPACAS’ existence is characterised by Brazil's efforts to rekindle it, thus reflecting its aspiration to create a new space of influence. Rather than pursuing more traditional forms of regional leadership, Brazil uses ZOPACAS as part of a persuasion-based strategy based on regional multilateralism that is designed in antagonism to other international organisations and Western powers. However, this strategy also faces important limitations resulting from resource constraints, lack of institutionalisation and an excessive exclusionary focus on minimising the role of global powers with interests in the region.